Using "Influential Persons" To Teach World History - Nielsen, Fred (Teaching History: A Journal of Methods, 2007)
The questions start early in the first class of the semester, smacking of curiosity with some hints of "what's in this for me?" "What's the point of learning about the past?" "What connection do dead people have to me?" Questions such as these, whether directly expressed or not, are the most basic ones that students bring to introductory history classes. They deserve answers.1